2022
DOI: 10.1111/cas.15571
|View full text |Cite
|
Sign up to set email alerts
|

Hsa‐microRNA‐370‐3p targeting Snail and Twist1 suppresses IL‐8/STAT3‐driven hepatocellular carcinoma metastasis

Abstract: The pro‐inflammatory factor interleukin‐8 (IL‐8) is related to poor prognosis in hepatocellular carcinoma (HCC) patients. Interleukin‐8 enhanced HCC invasion by upregulating Snail and Twist1, whether this modulation relies on microRNAs (miR) is unclear. In this study, hsa‐miR‐370‐3p was screened as candidate miRNA targeting Snail and Twist1, and its expression was downregulated by IL‐8. Luciferase assays and RNA electrophoretic mobility shift assays were used to evaluate the interaction between miR‐370‐3p and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…In addition, there are numerous extra-cardiac disease processes that may be affected by such genetic manipulation, the effects of which are hard to account for. For example, miR-370 has also been shown to play a regulatory role in various cancers, including cervical, ovarian, lung, gastric, and hepatocellular, among many others [ 156 , 157 , 158 , 159 , 160 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are numerous extra-cardiac disease processes that may be affected by such genetic manipulation, the effects of which are hard to account for. For example, miR-370 has also been shown to play a regulatory role in various cancers, including cervical, ovarian, lung, gastric, and hepatocellular, among many others [ 156 , 157 , 158 , 159 , 160 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, miR-370-3p binds to the 3′-UTR of Snail and Twist1, suppressing HCC metastasis. On the other hand, IL-8 stimulates STAT3 signaling to reduce miR-370-3p expression in mediating tumorigenesis [ 166 ]. Moreover, STAT3 increases the level of miR-23a to prevent gluconeogenesis in HCC [ 167 ].…”
Section: Non-coding Rnas Regulating Stat3 In Hccmentioning
confidence: 99%
“…Several miRNAs, such as miR-509-3p ( Zhang et al, 2021 ), miR-361-5p ( Yin et al, 2020 ), and miR-370-3p ( Peng et al, 2022 ), have been found to inhibit TWIST1 expression via targeting its 3′UTR and to abate the EMT process. Li et al (2022) observe that LINC00992 downregulates miR-361-5p and upregulates TWIST1, thus promoting cell proliferation, migration, and invasion.…”
Section: Emt-related Ncrnas Mechanisms Of Actionmentioning
confidence: 99%
“… Li et al (2022) observe that LINC00992 downregulates miR-361-5p and upregulates TWIST1, thus promoting cell proliferation, migration, and invasion. In addition, miR-370-3p decreases TWIST1 and SNAIL, affecting interleukin 8 (IL-8) expression and restraining the metastasis capacity in HCC cells ( Peng et al, 2022 ). In contrast, LINC01133 ( Yin et al, 2021 ) and lnc-UCID ( Yuan et al, 2021 ) increase EMT by acting as a sponge of miRNAs, increasing SNAIL expression.…”
Section: Emt-related Ncrnas Mechanisms Of Actionmentioning
confidence: 99%